Using blood biomarkers and ophthalmological indicators of optical coherence tomography and angiography for the diagnosis of fundus lesions in patients with diabetes mellitus - Huang, Fanny; Yu, Miaomiao; Huang, Laura; Wang, Ruikang K.; Leng, Theodore; Wang, Sophia Y.; Liao, Yaping Joyce (Frontiers in Clinical Diabetes and Healthcare, 2025)
PurposeTo assess long-term ophthalmic and clinical blood test changes in patients with different severities of diabetic retinopathy (DR).MethodsWe performed a longitudinal case-control study of 130 patients with diabetes mellitus (DM) and 67 controls, including visual acuities from 2,201 eye clinic visits and 44,833 blood tests. We also analyzed optic disc and macular structure and vasculature using optical coherence tomography (OCT) and angiography (OCTA).ResultsNinety-one percent of eyes in diabetic patients had stable visual acuity (better than 20/40) over 7 years. Cluster analysis revealed most prominent blood test changes in the DM included elevated glucose and hemoglobin A1c and evidence of nephropathy. Optic disc OCTA was most correlated with OCT in the superior and inferior quadrants. Notably, peripapillary and macular OCTA measurements revealed evidence of microvascular drop out even in those with DR grade 0.ConclusionsMajority of patients with DM monitored by physicians maintained good visual acuity over years. Ophthalmic imaging revealed evidence of early vascular changes even in patients without evidence of DR on clinical exam and color fundus imaging. In addition to ophthalmic functional and structural assessments, clinical blood tests for renal function are also important early biomarkers of end organ damage in DM.